Penilaian mutu asuhan keperawatan sebelum dan sesudah penerapan clinical pathway di Rumah Sakit Umum Pusat (RSUP) Sanglah, Bali, Indonesia - I Made Artana; Putu Ayu Indrayathi; I Made Ady Wirawan (DiscoverSys Inc., 2020)
Background: Hospitals implement clinical pathways in an effort to improve the quality of health services, especially the quality of nursing care. This study aims to determine whether the quality of nursing care after the application of the clinical pathway is better than the quality of nursing care prior to the clinical pathway application.Methods: This study used 180 inpatient medical records in January 2017-May 2019 with five priority medical diagnoses namely cerebral concussion and epidural hematoma (conservative therapy), conservative treatment of preterm premature rupture of membranes, ablation of atrioventricular nodal reentrant tachycardia (AVNRT) , atrioventricular reentrant tachycardia (AVRT), atrial tachycardia, atrial fibrillation, premature ventricular contractions (PVC), ventricular tachycardia (VT), junctional tachycardia and intracerebral haemorrhage (hemorrhagic stroke) as well as post-Lapastomy frozen section in the selected cystic ovary with a selective curative cyst . The variables studied were the application of clinical pathway, quality of nursing care, quality of assessment, diagnosis, planning, implementation and evaluation of nursing. Data were analyzed with the Pearson Chi-Square Test on SPSS version 17 for Windows.Results: The quality of good nursing care before and after the application of clinical pathway was 15.2% versus 50.9% (p = 0.00); good quality of nursing assessment before and after clinical pathway application of 6.7% versus 64.9% (p = 0.00); good quality of diagnosis before and after clinical pathway application of 72.7% versus 73.7% (p = 0.889); the quality of the nursing plan which consisted of good quality of goal formulation before and after the application of clinical pathway was 75.8% versus 73.7% (p = 0.759); good quality determination of interventions before and after clinical pathway application of 75.8% versus 79.8% (p = 0.523), good quality of implementation before and after clinical pathway application of 100% versus 100% and good quality of nursing evaluation before and after the application of clinical pathway is 100% versus 100%.Conclusion: The quality of nursing care and nursing assessment after the implementation of clinical pathway is significantly better than before the implementation of clinical pathway, while no significant difference was found in the quality of diagnosis, planning, implementation and evaluation of nursing. Latar Belakang: Rumah sakit menerapkan clinical pathway dalam upaya meningkatkan mutu pelayanan kesehatan khususnya mutu asuhan keperawatan. Penelitian ini bertujuan untuk mengetahui apakah mutu asuhan keperawatan sesudah penerapan clinical pathway lebih baik daripada mutu asuhan keperawatan sebelum penerapan clinical pathwayMetode: Penelitian ini menggunakan 180 rekam medis pasien rawat inap pada bulan Januari 2017-Mei 2019 dengan lima diagnosis medis prioritas yaitu cerebral concussion dan epidural hematoma (terapi konservatif), penanganan konservatif ketuban pecah dini preterm, ablasi pada atrioventricular nodal reentrant tachycardia (AVNRT), atrioventricular reentrant tachycardia (AVRT), atrial takikardi, atrial fibrilasi, premature ventricular contractions (PVC), ventricular tachycardia (VT), junctional takikardi dan intracerebral haemorrhage (stroke hemoragik) serta post laparatomi frozen section pada kista ovarii curiga ganasyang dipilih dengan purposive sampling. Variabel yang diteliti adalah penerapan clinical pathway, mutu asuhan keperawatan, mutu pengkajian, penegakan diagnosis, rencana, implementasi dan evaluasi keperawatan. Data dianalisis dengan Uji Pearson Chi-Square pada SPSS versi 17 untuk Windows.Hasil: Mutu asuhan keperawatan yang baik sebelum dan sesudah penerapan clinical pathway sebesar 15,2% versus 50,9% (p=0,00); mutu pengkajian keperawatan yang baik sebelum dan sesudah penerapan clinical pathway sebesar 6,7% versus 64,9% (p=0,00); mutu penegakan diagnosis yang baik sebelum dan sesudah penerapan clinical pathway sebesar 72,7% versus 73,7% (p=0,889); mutu rencana keperawatan yang terdiri mutu perumusan tujuan yang baik sebelum dan sesudah penerapan clinical pathway sebesar 75,8% versus 73,7% (p=0,759); mutu penentuan intervensi yang baik sebelum dan sesudah penerapan clinical pathway sebesar 75,8% versus 79,8% (p=0.523), mutu implementasi yang baik sebelum dan sesudah penerapan clinical pathway sebesar 100% versus 100% dan mutu evaluasi keperawatan yang baik sebelum dan sesudah penerapan clinical pathway sebesar 100% versus 100%.Simpulan: Mutu asuhan keperawatan dan pengkajian keperawatan sesudah penerapan clinical pathway secara signifikan lebih baik daripada sebelum penerapan clinical pathway, sedangkan mutu penegakan diagnosis, rencana, implementasi dan evaluasi keperawatan tidak terdapat perbedaan yang signifikan.